2021
DOI: 10.3390/cells10092272
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian-Cancer-Associated Extracellular Vesicles: Microenvironmental Regulation and Potential Clinical Applications

Abstract: Ovarian cancer (OC) is one of the most diagnosed gynecological cancers in women. Due to the lack of effective early stage screening, women are more often diagnosed at an advanced stage; therefore, it is associated with poor patient outcomes. There are a lack of tools to identify patients at the highest risk of developing this cancer. Moreover, early detection strategies, therapeutic approaches, and real-time monitoring of responses to treatment to improve survival and quality of life are also inadequate. Tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 154 publications
0
25
0
Order By: Relevance
“…In ovarian cancer, protein and miRNA are the main objects of sEV components considered as biomarkers for diagnosis and/or prognosis and are closely correlated to drug resistance, tumor microenvironment, and immune regulation [ 27 ]. We established a three-protein model for liquid biopsy for ovarian cancer with minimal loss of diagnostic efficacy, which showed good diagnostic efficacy even in the early-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, protein and miRNA are the main objects of sEV components considered as biomarkers for diagnosis and/or prognosis and are closely correlated to drug resistance, tumor microenvironment, and immune regulation [ 27 ]. We established a three-protein model for liquid biopsy for ovarian cancer with minimal loss of diagnostic efficacy, which showed good diagnostic efficacy even in the early-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although malignant cells themselves are the major source of tumorigenesis, their interactions with the tumor microenvironment are critical for the progression from a single tumor mass to distant metastases [26]. It was shown that exosomes carry messages (proteins, non-coding RNA, DNA, lipids, metabolites) from transformed healthy cells or to other cells in the tumor or they may signal in an autocrine manner back to the producing tumor cells causing changes in the recipient cells behavior and microenvironment alterations [27][28][29][30][31]. Moreover, cargo of exosomes from tumor microenvironments such as ascites fluids has been found to be highly immunosuppressive [32][33][34], helping cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that the proteomic profile of EXs can act as a useful tool or biomarker for diagnosing various types of cancer ( Nuzhat et al, 2017 ; Sharma et al, 2017 ; Kok and Yu, 2020 ; Croft et al, 2021 ). For example, a study by Klein-Scory et al (2014) illustrated that EXs secreted from pancreatic cancer cells had a distinctive proteomic profile allowing for possible use as an early stage biomarker ( Klein-Scory et al, 2014 ).…”
Section: New Advances In the Screening Of Ovarian Cancermentioning
confidence: 99%